2020
DOI: 10.1021/acs.jafc.0c04333
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Small Molecular Property on Antibody Response

Abstract: Antibodies with high titer and affinity to small molecule are critical in the field for the development of vaccines against drugs of abuse, antidotes to toxins and immunoassays for compounds. However, little is known regarding how properties of small molecule per se influence and which chemical descriptor could indicate the degree of the antibody response. Based on our previous study, we designed and synthesized two groups of small molecules, called haptens, with varied hydrophobicities to investigate the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Hapten structure determines the specificity and affinity of the resulting antibody [ 30 ]. To produce the antibody that could recognize ABZs, the characteristic structure of these compounds should be maximumly exposed to immune system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hapten structure determines the specificity and affinity of the resulting antibody [ 30 ]. To produce the antibody that could recognize ABZs, the characteristic structure of these compounds should be maximumly exposed to immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Critical molecular descriptors were finally compared as shown in Table 3 . Studies have shown that molecular parameters such as lipid-water partition coefficient (Log P , a widely used measure of hydrophobicity), dipole moments (μ, represents the polarity of molecule, the larger the polarity, the stronger the hydrophilicity), and topological polar surface area (TPSA) of analytes are important factors affecting recognition by antibodies [ 34 , 35 , 36 ], and hydrophobic force was believed to be the main driving force between small molecules and antibody [ 30 , 34 ]. In this study, Log P was found to be positively correlated with antibody affinity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge to develop assays based on the recognition of metabolites by antibodies firstly lies in the possibility to derive these small chemical molecules, to make them haptens (i.e., to link them covalently to carrier proteins whose role is to provoke/favor the immune response in immunized animals, naturally not immunogenic). In some cases, complex coupling chemistry procedures are necessary to obtain an immunogen [ 157 ]. Furthermore, antibodies of interest have to be selected on their specificity to recognize exclusively the molecule, without recognition of the derived molecule, or of related molecules.…”
Section: Alternative Tools To Mass Spectrometry and Nuclear Magnetic Resonance Instruments For Making Metabolomics Valuable In Clinical Lmentioning
confidence: 99%